Analysis of Configuration of Stinger Angle with Depth Variation During Installation On Pipe Diamater 20" in Banyu Urip, Bojonegoro - Imam Rochani; Juniavi Dini Kumala Putri; Handayanu Handayanu (International Journal of Offshore and Coastal Engineering (IJOCE), 2017)
The selection of subsea pipeline construction methods used depends on the environmental conditions and behavior of the pipe installation system which acquires a variety of loads during installation and may the result in failure. In this case the required angle stinger configuration is in accordance with the criteria to avoid overstress and local buckling on the pipe during installation, the variation of the depth of 15 meters, 18 meters, 20.65 meters, 21.25 meters and 22.25 meters can help analysis the stress on the pipe in each case. The pipeline is 23.4 km north of Bojonegoro. From the results of the analysis, it is known that the configuration of stinger angles used during installation for each water depth is 15 m with stinger angle 8.88 degree, 18.65 m stinger angle 8.88 degree, 20.65 m stinger angle 8.88 degree, 21.25 m stinger angle 8.88 degree and 22.25 m stinger angle 8.88 degree. The result of pipe stress on the overbend area has a value of 85.13% SMYS or 352.42 Mpa when the direction of wave comes 90 degrees, while the sagbend area of the pipe has a maximum stress of 51.01% SMYS or 211.2 Mpa when the direction of wave comes 180 degrees. Local buckling check results in all conditions show safe results during the installation process.